2017
DOI: 10.1038/s41598-017-12779-5
|View full text |Cite
|
Sign up to set email alerts
|

Short term changes in the proteome of human cerebral organoids induced by 5-MeO-DMT

Abstract: Dimethyltryptamines are entheogenic serotonin-like molecules present in traditional Amerindian medicine recently associated with cognitive gains, antidepressant effects, and changes in brain areas related to attention. Legal restrictions and the lack of adequate experimental models have limited the understanding of how such substances impact human brain metabolism. Here we used shotgun mass spectrometry to explore proteomic differences induced by 5-methoxy-N,N-dimethyltryptamine (5-MeO-DMT) on human cerebral o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
88
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(103 citation statements)
references
References 84 publications
(85 reference statements)
1
88
0
1
Order By: Relevance
“…This effect has been demonstrated following induction of inflammation in human primary monocyte-derived dendritic cells pretreated with 100 μM of DMT (Szabo et al, 2014 ). Similar involvement of DMT in inflammation pathways was reported by Dakic et al ( 2017 ), who tested broad changes in the human neural proteome following 5-MeO-DMT application utilizing human cerebral organoids. They reported several differences in protein expression between vehicle (0.3% ethanol) and treatment group (24-h incubation with 5-MeO-DMT) via mass spectrometry.…”
Section: Inmt Polymorphisms Identified In Genetic Screenssupporting
confidence: 72%
See 1 more Smart Citation
“…This effect has been demonstrated following induction of inflammation in human primary monocyte-derived dendritic cells pretreated with 100 μM of DMT (Szabo et al, 2014 ). Similar involvement of DMT in inflammation pathways was reported by Dakic et al ( 2017 ), who tested broad changes in the human neural proteome following 5-MeO-DMT application utilizing human cerebral organoids. They reported several differences in protein expression between vehicle (0.3% ethanol) and treatment group (24-h incubation with 5-MeO-DMT) via mass spectrometry.…”
Section: Inmt Polymorphisms Identified In Genetic Screenssupporting
confidence: 72%
“…The use of human cerebral organoid models in teasing apart which ligands activate which pathways may prove useful, as these systems are made up of heterologous cell clusters capable of differentiating into tissues containing the cellular makeup of broad brain regions. These cultures include multiple neuronal cell types and proteins where DMT interacts including sigma-1 and 5-HT2A/C receptors, and are thus more representative of an in vivo neuronal system (Dakic et al, 2017 ).…”
Section: Endogenous Dmt and The Transmethylation Hypothesismentioning
confidence: 99%
“…The nuclear factor kappa-B (NFKB) pathway seems to be critically involved in the epigenetic underpinnings of memory reconsolidation via increasing global histone H3 phosphorylation and acetylation ( Lubin and Sweatt, 2007 ). Significantly, the DMT analogue 5-methoxy- N,N -dimethyltryptamine as well as the synthetic psychedelic 2,5-Dimethoxy-4-iodoamphetamine downregulate this pathway, suggesting that DMT and Ayahuasca might present at least same degree of NFKB pathway modulation ( Yu et al, 2008 ; Dakic et al, 2017 ). It could therefore be argued that Ayahuasca enhances the process of memory reconsolidation via modulating NFKB-mediated regulation of epigenetic modification at the histone level.…”
Section: Memory Ptsd and Traumatic Memoriesmentioning
confidence: 99%
“…To the best of the author’s knowledge, no study has investigated the effects of Ayahuasca or other psychedelic compounds on processes involving epigenetic regulation of gene expression. However, studies investigating gene expression changes stemming from LSD and proteomic changes induced by the DMT analogue 5-MeO-DMT have been reported ( Nichols and Sanders-Bush, 2002 ; Nichols et al, 2003 ; Dakic et al, 2017 ). An early investigation into long-term Ayahuasca drinkers suggested that long-term Ayahuasca consumption increases 5HT binding sites in platelets ( Callaway et al, 1994 ).…”
Section: Future Directionsmentioning
confidence: 99%
“…DMT and 5-MeO-DMT have also been shown to exert potent anti-inflammatory effects through the modulation of innate and adaptive immune processes (Szabo 2015;Szabo et al 2014). Moreover, in vitro studies have recently provided evidence of anti-inflammatory, neuroregenerative, and anti-addictive effects induced by 5-MeO-DMT (Dakic et al 2017). In addition, 5-MeO-DMT has been demonstrated to affect neurogenesis, which may contribute to the known antidepressant properties of DMT-derived compounds (Lima et al 2018).…”
Section: Introductionmentioning
confidence: 99%